2016
DOI: 10.1002/cjas.1411
|View full text |Cite
|
Sign up to set email alerts
|

Quick decisions tend to reinforce self‐interest choices among MBA students: The direct and moderating effects of temporal constraint and situational factors in ethical decision making

Abstract: Employees face increasingly time-pressured operational environments. Using theory from Reynolds ' (2006) neurocognitive model of ethical decision making, we explore how temporal constraint, consequence framing, and organizational norms affect self-interested decision making in business. Conducting three experimental manipulations with a sample of MBA students, we found the following: First, consistent with previous studies, high time pressure promotes self-interested intentions. Second, unethical framing enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Accordingly, the results do not confirm our hypotheses. The negative association between time pressure and moral behavior stands in line with a great number of studies, showing that time pressure indeed elicits unethical behavior (Andiappan & Dufour, 2016;Belle & Cantarelli, 2017;Koh et al, 2011Koh et al, , 2018. Nevertheless, it is of high importance to not assume that time pressure axiomatically impairs ethical decision-making.…”
Section: Discussion Of Empirical Findingssupporting
confidence: 72%
See 2 more Smart Citations
“…Accordingly, the results do not confirm our hypotheses. The negative association between time pressure and moral behavior stands in line with a great number of studies, showing that time pressure indeed elicits unethical behavior (Andiappan & Dufour, 2016;Belle & Cantarelli, 2017;Koh et al, 2011Koh et al, , 2018. Nevertheless, it is of high importance to not assume that time pressure axiomatically impairs ethical decision-making.…”
Section: Discussion Of Empirical Findingssupporting
confidence: 72%
“…The absence of differences in moral behavior between Type As and Type Bs might again be explained by self-serving choices. As the study of Andiappan and Dufour (2016) revealed, individuals take more self-serving choices when put under time constraints. The investigation of further revealed that Type As stick to their strong belief in own competences, even when the situation is unclear.…”
Section: Discussion Of Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation